Clinical Aspects of Amniotic Membrane Implants in Corneal Repair in Dogs with Complicated Ulcers - Rozin, Adriano (2020)
Background: Among numerous disorders treated by veterinary ophthalmology, therapies employed to solve corneal ulcers stand out. Amniotic membrane transplantation is an effective surgical technique for the treatment of complicated corneal ulcers in the dog, with highly satisfactory visual and cosmetic outcomes. However, in veterinary ophthalmology, reports on the use of the amniotic membrane and its corneal reconstructive potential are scarce. The objective of this work was to evaluate, for 21 days, the clinical aspects and the effectiveness of transplantation of canine amniotic membrane for corneal healing in two cases of complicated ulcers in dogs. Cases: Two Shih-Tzu dogs were diagnosed with complicated corneal ulcer. They underwent surgical treatment with the use of a glycerin-preserved canine amniotic membrane implant, which was secured on the cornea or the limbus. A surgical microscope at a magnification of 16x was used. The devitalized tissues at the periphery of the ulcer were excised, and multiple layers of amniotic membranes were sutured onto the cornea and near the limbus with interrupted absorbable suture. Protection of the canine amniotic membrane implants was performed with a scarified third eyelid flap, which was attached to the upper eyelid, and maintained for 14 days. During the first 14 days after the procedure, topical treatment with antibiotic eye drops was administered; protease inhibitors were also used. Antibiotics were used systemically for 10 days. Between days 14 and 21 after the transplantation procedure, protease inhibitors, corticosteroids, and lubricant were administered topically. Healing and clinical aspects were evaluated on days 0, 14, and 21. The parameters evaluated were blepharospasm, dazzle and direct pupillary reflexes, and consensual and threat responses. Corneal vascularization, hypopyon, synechia, opacity, and fluorescein dye penetration into the cornea were evaluated. The patient whose membrane was attached to the cornea was named COr, and the animal whose membrane was attached to the corneal limbus was named PLi. Blepharospasm and positive fluorescein test were detected only on the first day of the experiment; whereas, the dazzle and pupillary reflexes, as well as the consensual response, were present in both animals at all evaluated time points. Only COr exhibited hypopyon on day 0. Synechia was not observed in any of the animals at any of the time points. On the 21st day, COr exhibited deep vascularization and an opaque scar, while PLi exhibited only discrete vessels without blood perfusion, secondary to corneal repair. Discussion: A smooth operation of the central and peripheral ophthalmic system was maintained at all periods evaluated. The protection provided by the membrane contributed to corneal healing by reducing stimulation of nerve endings on the epithelium and stroma, and suppressing the blepharospasm reflex. The amniotic membrane used as an adjuvant has antimicrobial and anti-inflammatory properties, inhibits proteinases and mediators of inflammation, and exerts a mechanically protective effect. The corneal vascularization observed in both animals is related to the healing processes stimulated by filling the deep corneal lesions with the membrane. When used in addition to drug therapy, the amniotic membrane can inhibit postinflammatory neovascularization, fibroblast activity, collagen deposition, scarring, and opacifications. Accurate diagnosis, and correct therapeutic and surgical management, is fundamental for the successful treatment of corneal ulcers. In this work, canine amniotic membrane preserved in glycerin was used for the surgical treatment of complicated ulcers in dogs along with adequate clinical therapy. This was effective independent of the different anchorage techniques used, and led to satisfactory clinical results and short-term corneal healing.